Pengaruh Konten Instagram Dear Me Beauty Terhadap Minat Beli Konsumen (Survei pada Followers Instagram @Dearmebeauty) - Wardatul Jannah; Aminah Swarnawati (STIKes Ibnu Sina Ajibarang, 2025)
The advancement of technology and the internet has driven the use of social media, including Instagram, as a communication and marketing tool. Dear Me Beauty utilizes Instagram to promote products and engage with consumers. This study aims to analyze the Instagram content of @dearmebeauty, examine consumer purchase interest, and measure the influence of Instagram content on purchase interest. A quantitative research method was employed using a survey of 91 active followers selected through Simple Random Sampling. Data was collected via an online questionnaire and analyzed using simple linear regression. The results indicate that Dear Me Beauty’s Instagram content significantly influences consumer purchase interest. This is evidenced by the t-value exceeding the t-table value, indicating a positive effect. The R Square value of 62.4% suggests that Instagram content contributes to purchase interest, while 37.6% is influenced by other factors not examined in this study. These findings highlight the crucial role of engaging Instagram content in shaping consumer purchase interest and provide insights for businesses to optimize their digital marketing strategies.